Determinants of Capital Structure: Evidence from Chinese firms - Akite, Jennifer (2017)
This study focused on investigating the determinant factors of corporate capital structure among Chinese listed firms. The sample data contained a total of 200 firms observed for a ten year period of 2007 to 2016. The dependent variable of this study, debt ratio was broken down into 3 parts and seven independent variables tested against them. Using panel data estimation method (OLS, fixed effects and random effects), a number of variable were found to be significant depending on the precise definition of leverage used. From the OLS regression, short term debt ratio was found to have a significant positive relationship with tangibility, size, profitability and earnings volatility but a negative relationship with non-debt tax shield. Long-term debt had a positive significant relationship with non-debt tax shield but a negative relationship with tangibility and volatility. Total debt was found to have a positive significant relationship with profitability, tangibility, size and non-debt tax shield. Also, from the analysis of the data, it was observed that Chinese listed firms mainly relied on short-term financing.